Tectonic evolution of the Northeastern Paleo-Tethys Ocean during the late Triassic: insights from depositional environment and provenance of the Xujiahe formation - Xie, Fenquan; Xiao, Wenzhou; Sami, Mabrouk; Sanislav, Ioan V.; Ahmed, Mohamed S.; Zhang, Chenguang; Wang, Yongkui; Yan, Bingpeng; Hu, Bing; Li, Ning; Fathy, Douaa (Frontiers in Earth Science, 2024)
The Triassic tectonic evolution and affinity among the Yangtze Block, Qinling Orogenic Belt and Songpan-Ganzi Terrane remain subjects of ongoing scientific debate. In this context, the sedimentary rocks of Xujiahe Formation (second segment) (T3x2) represent an ideal case for addressing this issue. In this study, new stratigraphic, geochemical and detrital zircon analyses have been conducted on two sections of the T3x2. The stratigraphic assemblage and features suggests a braided delta as the depositional setting. Whole-rock geochemical results indicate that the sandstones from the T3x2 exhibit moderate palaeo-weathering and primarily originate from upper crustal felsic rocks, mostly S-type granites. The detrital zircons within these sandstones display distinctive age peaks at intervals of 200-300 Ma, 700-900 Ma, and 1800-2000 Ma, similar to those from the Qinling Orogenic Belt. Both the clastic particle composition and whole-rock geochemistry indicate that the T3x2 sections were deposited in a transitioning from a passive to an active continental margin, highlighted by a braided delta influenced by rivers flowing from the northeast to the southwest.